Histological and Histomorphomitrical Evaluation of Rabbit Oral Cavity Wound Healing by Feeding Absorbable Amino Acid - Manar Abd Alrazaq Hassan (Diyala Journal of Medicine)
Background: Traumatic oral ulcer is well-circumscribed, depressed lesion with an epithelial defect that is covered by a fibrin clot, resulting in a yellow-white appearance, occurs due to chemical, mechanical or thermal injury to oral mucosal end with painful erosion. Amino acids are necessary for wound healing because they promote the growth of connective tissue as well as the activation and proliferation of fibroblasts.